Whole-Body Vibration Exposure Of Malaysian Taxi Drivers - Ahmad Rasdan, Ismail; S. N. A., Abdullah; Abdul Adam, Abdullah; B. M., Deros (Universiti Malaysia Pahang, 2015)
During their whole working time, taxi drivers are usually seated. Additionally, longterm exposure to whole-body vibration while driving may lead to diseases and adverse health conditions such as lower-back pain. The objective of this study is to investigate the relationship between measurable whole-body vibration and lower-back pain. This study was conducted on two highways: Kuala Lumpur–Karak Highway and the North– South Highway. A tri-axial seat accelerometer was placed at the point of contact between the driver and the seat pad. The assessment of whole-body vibration measurement is according to ISO 2631-1. Excessive whole-body vibration has been evidenced as leading to lower-back pain. Taxi drivers are recommended to drive no more than the allowable exposure limit. In this study, the whole-body vibration does not exceed the allowable exposure limit. Therefore, the taxi drivers in this study do not have lower back pain.